2015
DOI: 10.1055/s-0034-1378945
|View full text |Cite
|
Sign up to set email alerts
|

How the Structural Elucidation of the Natural Product Stephanosporin Led to New Developments in Aryl Radical and Medicinal Chemistry

Abstract: The intent of this account is to provide a focused overview of recent developments in aryl radical chemistry, especially extensions and applications of the Meerwein arylation and the Gomberg-Bachmann reaction. Although most of the reactions and methods described were discovered on the basis of earlier findings made by our group or logically depend on newly discovered reactivities or mechanistic principles, the rapid evolution of radical chemistry can nevertheless be traced back to the behavior of the natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Here, we chose gold( i ) chloro derivatives [AuCl(PR 3 )] containing PR 3 as ligands: PPh 3 ( 1 ) and PEt 3 ( 2 ), 36 as the compounds to be encapsulated into liposomes (structures in Fig. S1‡).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we chose gold( i ) chloro derivatives [AuCl(PR 3 )] containing PR 3 as ligands: PPh 3 ( 1 ) and PEt 3 ( 2 ), 36 as the compounds to be encapsulated into liposomes (structures in Fig. S1‡).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds ([AuCl(PPh 3 )] ( 1 ), [AuCl(PEt 3 )] ( 2 ) and [AuCl(BODIPY-PPh 2 )] ( 3 ) respectively), were all synthesized as reported. 36,55,58 2-Iminothiolane (Traut's reagent) and the ELISA kit were purchased from Sigma-Aldrich. Trastuzumab and pertuzumab were purchased in-house at Memorial Sloan Kettering Cancer Center.…”
Section: Methodsmentioning
confidence: 99%
“…The aryl radical addition to aromatic compounds with aryl diazonium salts, which was first discovered by Gomberg and Bachmann, is a highly useful method for synthesizing unsymmetrical biaryls. Several outstanding reviews have discussed biaryl synthesis with arene diazonium salts over the past six years. This radical-type C–H bond arylation has attracted interest from the synthetic community. , Recent advances in this area mainly focus on developing transition-metal-catalyzed, organic initiator-mediated, photoinduced, and electrolysis processes (Scheme ). The transition-metal-catalyzed C–H bond functionalization and dual photoredox/transition-metal-catalyzed approaches will be summarized in the following section.…”
Section: Aryl C–c Bond Formationsmentioning
confidence: 99%
“…58−63 This radical-type C−H bond arylation has attracted interest from the synthetic community. 64,65 Recent advances in this area mainly focus on developing transitionmetal-catalyzed, organic initiator-mediated, photoinduced, and electrolysis processes (Scheme 23). The transition-metalcatalyzed C−H bond functionalization and dual photoredox/ transition-metal-catalyzed approaches will be summarized in the following section.…”
Section: Aryl C−c Bond Formations 21 Aryl C−c Bond Formations Involvi...mentioning
confidence: 99%
“…We report herein the development of a tin‐free strategy that uses phenylboronic acids to mediate the three‐component carbocyanation of olefins and the vinylation of alkyl halides under radical conditions. It has been shown that alkyl radicals may be selectively generated through the rapid abstraction ( k ≈ 10 9 m –1 s –1 ) of the iodine atom from an alkyl iodide by an aryl radical, which is formed by the fragmentation of arylboronic acids under oxidative conditions . This fast abstraction outperforms other competitive processes that might occur in the medium, including the addition to sulfonyl derivatives or the olefin partner .…”
Section: Introductionmentioning
confidence: 99%